Increasing Teachers' Capabilities Through Academic Supervision Using The Tsaabita Method In Learning To Read And Write The Qur'an At MI Ma'arif Gedangan - Mushbihah Rodliyatun; Adi Hermawan; Muh. Fatoni; Muchammad Zaidun (CV. Syntax Corporation Indonesia, 2021)
This research is quantitative research, using descriptive analysis method that is supported by data obtained through field research or by direct survey, research that looks at the description of an existing phenomenon, namely collecting data and facts from the object being studied. investigated by distributing questionnaires to respondents at a predetermined research location. The result of the research is that the level of teacher ability through academic supervision using the tsaabita method in learning to read and write Al-Qur'an MI Ma'arif Gedangan, Tuntang sub-district, Semarang district can be seen that students who have a low BTA ability level are 31 students or 28.70%, the level of There are 61 students or 56.48% of medium BTA abilities, and 16 students or 14.81% of high BTA abilities. These results indicate that some of the BTA ability levels of MI Ma'arif Gedangan students are in the medium category. The level of BTA ability of MI Ma'arif Gedangan students based on each question item can be seen that the BTA ability level of MI Ma'arif Gedangan students based on hijaiyah letters is in the medium category, in punctuation (harakat) is in the medium category, based on tajwid (law of reading). ) in the medium category and based on reading and writing the Qur'an in the high category. This research aims to improve the ability of teachers through academic supervision using the tsaabita method in learning to read and write the Qur'an at MI Ma'arif Gedangan Tuntang Kab. Semarang District